2020
DOI: 10.1186/s12879-020-05031-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of drug resistant Mycobacterium tuberculosis in Africa: a systematic review

Abstract: Background: The burden of drug resistant tuberculosis in Africa is largely driven by the emergence and spread of multidrug resistant (MDR) and extensively drug resistant (XDR) Mycobacterium tuberculosis strains. MDR-TB is defined as resistance to isoniazid and rifampicin, while XDR-TB is defined as MDR-TB with added resistance to any of the second line injectable drugs and any fluoroquinolone. The highest burden of drug resistant TB is seen in countries further experiencing an HIV epidemic. The molecular mecha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 90 publications
0
23
0
Order By: Relevance
“…However, yet another study from China found that defaulting rate is 17% and a higher defaulting rate was also reported from Africa and India [ 28 , 29 ]. Defaulted M/XDR-TB patients could potentially continue to infect others and are a threat to public health, just as Chisompola et al reported that primary drug resistance remained the predominant type of transmission [ 30 ]. Therefore, reducing defaulting rate is critical to reduce M/XDR-TB spread.…”
Section: Discussionmentioning
confidence: 99%
“…However, yet another study from China found that defaulting rate is 17% and a higher defaulting rate was also reported from Africa and India [ 28 , 29 ]. Defaulted M/XDR-TB patients could potentially continue to infect others and are a threat to public health, just as Chisompola et al reported that primary drug resistance remained the predominant type of transmission [ 30 ]. Therefore, reducing defaulting rate is critical to reduce M/XDR-TB spread.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the major risk causes that have been linked with hospital-acquired DR-TB are lack of proper TB infection prevention and control measures, poor ventilation, delayed diagnosis, and overcrowded wards [ 61 ]. In nations with high HIV occurrence rate, over 75% of tuberculosis cases are HIV-associated [ 62 ] and the high rate of HIV prevalence rate in TB infected persons makes nosocomial spread or transmission a major driving force in the transmission of DR-TB strains [ 63 ]. Another method used to analyse a research field is the use of a co-word.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is the need to further assess the complexity of the emergence of drug resistant strains that have become a major challenge to the control of the disease. Comparative genomic studies have also shown that strain diversity could also be a major factor heightening the threat of TB drug resistance (40,178,179). This section seeks to throw more light on the advances made toward deciphering the mechanisms of drug resistance especially among the West African genotypes of MTBC and to provide new directions for future studies.…”
Section: Mechanism Of Drug Resistance Emergence and Evolutionmentioning
confidence: 99%
“…There is paucity of data on TB drug resistance in sub-Saharan Africa which has always called for active surveillance to determine the true burden of DR in West Africa and Africa as a whole (178). The WHO initially reported the burden of drug resistance in West Africa based mainly on projected estimates.…”
Section: Mechanism Of Drug Resistance Emergence and Evolutionmentioning
confidence: 99%